Os efeitos das tecnologias digitais aplicadas ao food service: fatores determinantes na experiência do cliente - Correa, Gabriele Moreira; Assuaga, Giovanna Corrêa (Universidade Federal de São Carlos, 2021)
The implementation of digital technologies is a trend that has been growing in the food services sector outside the home in Brazil. In order to understand this scenario, this work aimed to identify and analyze the factors that impact the experience of customers with the use of digital technologies in the food service sector. A quantitative research approach was adopted, in which data were collected through a survey questionnaire. The sample consisted of consumers who have already attended food service establishments that use some of the following self-service technologies: digital menus, available on mobile devices coupled in the center of the table and /or self-service totems. The results showed that most customers had positive experiences with the use of digital technologies in food service, where the factors considered most important in the research were speed and efficiency and ease and simplicity. Despite the positive experiences, the interviewees showed low willingness to face queues or pay more in restaurants that use self-service technologies and, most did not consider fun and pleasure relevant to their experience, making them the least important factors identified in this study. With the realization of this research, it was possible to clarify the impact factors in the consumer experience with technological applications in food service, bringing theoretical contributions, by exploring a topic little addressed in the Brazilian context, and managerial, by serving as a basis for making decisions about the implementation of new digital technologies of self-service, as well as for understanding the preferences and expectations of customers.
The effects of digital technologies applied to food service: determinant factors in the customer 's experience
Keywords: Food service; Food service; Tecnologias digitais; Experiência do cliente; Satisfação do cliente; Tecnologia de autoatendimento; Digital technologies; Customer experience; Customer satisfaction; Self-service technology; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS